Rekonstruksi Kebijakan Wajib Belajar Menjadi 13 Tahun sebagai Pemenuhan Sustainable Development Goals di Indonesia - Intan Permata Sari; Slamet Tri Wahyudi (Lembaga Yasin AlSys, 2025)
Poverty remains a structural issue in Indonesia that demands sustained policy intervention, particularly in the education sector. One key poverty alleviation strategy emphasized by welfare states is the expansion of access to education. This study aims to analyze the urgency of reconstructing the compulsory education program from 12 to 13 years within the framework of legal principles and sustainable development. A normative juridical method was employed, utilizing statutory and conceptual approaches. The findings reveal that compulsory education represents the fulfillment of human rights as guaranteed by various national legal instruments, including Government Regulation No. 47 of 2008. The reconstruction of compulsory education to 13 years is viewed as a concrete effort by the state to reinforce its role in ensuring the right to education and its commitment to the Sustainable Development Goals (SDGs), particularly Goal 4 on quality education. The implementation of 13 years of compulsory education also holds strategic implications for preparing the 2045 Golden Generation by ensuring more inclusive and equitable access to education. Therefore, the expansion of compulsory education is not merely an educational policy, but also a structural instrument for building a more prosperous and competitive society.